Experimental Study of the Dynamic Compressive and Tensile Strengths of Fly Ash and Slag Based Alkali-Activated Concrete Reinforced With Basalt Fibers - Lian, Chong; Wang, Yubo; Liu, Shan; Hao, Yifei (Frontiers in Materials, 2021)
The use of industrial by-products, e.g. fly ash, slag, as complete replacement of Portland cement to make alkali-activated concrete (AAC) has become a hot topic due to the contribution to sustainability in construction industry. AAC has comparable compressive strength compared to the ordinary Portland cement concrete (OPC) and has many advantages, such as excellent durability and corrosion resistance. However, similar to OPC, AAC material still has certain shortcomings such as brittleness, low tensile strength, and poor impact resistance, which can be improved by incorporating fibers in the matrix. This paper considers the basalt fiber-reinforced alkali-activated concrete (BFRAAC), and explores the dynamic compressive and tensile strengths through a series of impact tests. The test results show that the dynamic strength of BFRAAC exhibits significant strain rate effect, that is, the material strength increases with the strain rate. Compared to the compressive strength of the material, the strain rate sensitivity of its tensile strength is more marked. Based on the test results, empirical formulas describing the relation between dynamic strength and strain rate of BFRAAC are proposed.